Relationship between carbon footprint and profits: the moderating role of clean energy innovation - Porles Ochoa, Francisco Daniel (2023)
Clean energy innovation is critical to the decarbonization of CO2-intensive industries that rely on fossil fuels. Nonetheless, a deeper understanding of the influence of technical innovation on firms' efforts to tackle climate change and improve economic competitiveness is needed, particularly in those industrial sectors with "hard-to-abate" CO2e emissions. This quantitative longitudinal research examines the moderating effect of clean energy innovation on the link between carbon footprint and corporate profits using a global sample of 7,827 firm-year data pertaining to 167 multinational companies between 2018 and 2021. This study uses the Bayesian method, a recommended statistical framework for fitting complex growth curve models with longitudinal data, to specify a multi-indicator latent growth curve (B-LGC) model for longitudinal moderation analysis. The findings indicate that the carbon footprint has a large positive influence on corporate profits. Furthermore, the model results support the prediction that clean energy innovation positively moderates the link between value chain (Scope 3) emissions and gross profit margin when measured using renewable energy consumption. The implications of the findings suggest that executives and managers in heavily polluting companies can achieve greater competitive advantages and transition to a net-zero emissions business by developing a comprehensive understanding of Scope 3 emissions. More significantly, policymakers should pay particular attention to these companies' Scope 3 emissions in order to develop regulation and control systems that encourage clean energy innovation.